ダイ 28 ジ ナンキョク チイキ カンソク タイ エットウ タイ ホウコク 1987-1988 - 大山, 佳邦; オオヤマ, ヨシクニ; Ohyama, Yoshikuni (1989)
P(論文) 第28次南極地域観測隊越冬隊は37名により構成された。うち29名は昭和基地において越冬観測に従事し, 残り8名はあすか観測拠点において初の越冬観測を行った。あすか観測拠点における活動はすでに別に報告されているので, ここでは昭和基地における活動を報告する。昭和基地の活動は1987年2月1日, 基地を引き継いでより, 1988年1月31日まで続けられた。その間, 定常観測のほかに今次隊から開始する2つの長期にわたる研究観測計画を発足させた。すなわち気水圏系による「南極における気候変動に関する総合研究」と生物・医学系による「陸上生態系構造の研究」とである。そのほか宙空系によるオーロラ観測や雪氷・地学系によるテレメトリーによる地震観測も実施された。また設営面では通常の基地を維持する活動のほか, 基地の整備にも努めた。1986年10月以降無人となったみずほ基地の維持にも努め, 発電施設などの保守, 点検も実施した。 The wintering party of the 28th Japanese Antarctic Research Expedition performed its activities at Syowa and Asuka Stations from 1987 to 1988. The wintering activities at Asuka Station had commenced from this season by eight men, and have already been reported by M. AYUKAWA. The wintering party at Syowa Station composed of 29 personnel has newly started two long-term scientific programs. One was the Antarctic Climate Research which was recommended by the Scientific Committee on Antarctic Research with reference to the World Climate Research Program. The other was the Studies of Terrestrial Ecosystems which was the Japanese program in response to the international program of Biological Investigations of Terrestrial Antarctic Systems. The routine and fundamental observations comprising aurora, geomagnetism, ionosphere, meteorology, oceanography and seismology were performed as in the preceding years. A seismic observation using the triangular telemetric system was carried out. Two circum-Antarctic balloons were launched in December 1987. departmental bulletin paper